Exploring organizationally directed citizenship behaviour: Reciprocity or ‘It’s my Job’? - Kessler, I; Coyle-Shapiro, J; Purcell, J (2004)
This study sets out to examine two explanations for why employees engage in organizational citizenship behaviour (OCB). The first explanation views OCB as a form of reciprocation where employees engage in OCB to reciprocate fair or good treatment from the organization. The second view is that employees engage in OCB because they define those behaviours as part of their job. The research methodology consisted of survey data from 387 hospital employees on their perceptions of procedural and interactional justice, mutual commitment, job breadth and OCB. The results suggest that procedural and interactional justice are positively associated with mutual commitment that in turn, is related directly to OCB and indirectly through expanding the boundaries of an individual's job. These findings suggest that together the reciprocation thesis and ‘it's my job’ argument complement each other and provide a more complete foundation for our understanding of OCB. The difference between the two perspectives lies in the process by which individuals respond; that is, role enlargement and role maintenance. Implications and directions for future research are discussed.